2015
DOI: 10.1002/2015rs005677
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between GPS radio occultation electron densities and in situ satellite observations

Abstract: Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) Global Positioning System (GPS) radio occultation (RO) electron densities are compared with collocated in situ observations from the CHAllenging Minisatellite Payload (CHAMP) and Communications/Navigation Outage Forecasting System (C/NOFS) satellites. The comparison is restricted to observations occurring within 2 ∘ latitude and longitude and 15 min local time. The in situ observations occur at altitudes of ∼300-800 km, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 23 publications
5
42
1
Order By: Relevance
“…Thus, some comparative studies between RO and ground‐based observations preferred analyses during geomagnetically quiet conditions [e.g., Chu et al , ; Wu et al , ] to avoid errors related to the occurrence of ionospheric electron density irregularities. However, other studies have done validation case studies on one storm period [e.g., Krankowski et al , ], while significant literature that exists performs statistics based on large data sets without necessarily doing any isolation based on geomagnetic activity or occurrence of ionospheric irregularities [e.g., Yue et al , ; Chuo et al , ; Pedatella et al , , and references therein]. These studies give an indication that RO data may be able to follow ionospheric dynamics even during geomagnetic storms, although not in a detailed quantitative sense.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some comparative studies between RO and ground‐based observations preferred analyses during geomagnetically quiet conditions [e.g., Chu et al , ; Wu et al , ] to avoid errors related to the occurrence of ionospheric electron density irregularities. However, other studies have done validation case studies on one storm period [e.g., Krankowski et al , ], while significant literature that exists performs statistics based on large data sets without necessarily doing any isolation based on geomagnetic activity or occurrence of ionospheric irregularities [e.g., Yue et al , ; Chuo et al , ; Pedatella et al , , and references therein]. These studies give an indication that RO data may be able to follow ionospheric dynamics even during geomagnetic storms, although not in a detailed quantitative sense.…”
Section: Introductionmentioning
confidence: 99%
“…Considering COSMIC data, the modified IRI‐2012 model leads to an improvement in estimating topside N e profiles. A recent global study comparing GPS radio occultation N e with in situ CHAMP and C/NOFS satellite observations for altitude range from near F 2 peak to topside ionosphere reported that the COSMIC is accurate at providing topside N e data [ Pedatella et al , ]. These authors also found errors within the low latitude and equatorial ionization anomaly regions resulting from the spherical symmetry assumption employed by the Abel inversion technique in deriving electron density profiles.…”
Section: Resultsmentioning
confidence: 99%
“…The f o F 2 values derived from EDPs will be compared with ionosonde measurements that will be taken as reference values to check the quality of the RO inversion. In this way, one can assess the error of the RO results by calculating the distribution of the relative difference with respect to ionosonde measurements: ΔritalicfoF2=italicfoF2ROitalicfoF2ionosondeitalicfoF2ionosonde0.25em Since early studies, this relative difference has been used as a metric for assessing the accuracy of f o F 2 retrievals (e.g., Hajj & Romans, ; Hernández‐Pajares et al, ; Schreiner et al, ) and more recently in Pedatella et al () or Habarulema and Carelse ().…”
Section: Data Tests and Metric Used For Comparisonsmentioning
confidence: 99%
“…Since early studies, this relative difference has been used as a metric for assessing the accuracy of f o F 2 retrievals (e.g., Hajj & Romans, 1998;Hernández-Pajares et al, 2000;Schreiner et al, 1999) and more recently in Pedatella et al (2015b) or Habarulema and Carelse (2016).…”
Section: Description Of the Testsmentioning
confidence: 99%